Multi-Product Quantity-Dependent Prices and Profitability Constraints - Spence, A. M. (Review of Economic Studies, 1980)
Focuses on a study which developed a formulae of optimal quantity-dependent pricing schemes for several products. Description of the single product model; Details on the Pareto optimality; Information on the multi-product pricing. (Из Ebsco)